Metastatic squamous cell carcinoma of the skin with clinical response to lapatinib - John D. Strickley; Aaron C. Spalding; M. Tye Haeberle; Timothy Brown; Don A. Stevens; Jae Jung (Experimental Hematology & Oncology, 2018)
Abstract Background Lapatinib is a tyrosine kinase inhibitor that blocks the HER2 receptor and is typically used in the setting of metastatic breast cancer. Both ERBB2 (HER2) and ERBB3 (HER3) belong to the same family of receptor tyrosine kinases. Dimerization of these receptors leads to activation of cell proliferation and survival pathways, granting oncogenic potential to dysregulated ERBB/HER receptors. Next generation sequencing (NGS) of tumors has ushered in a new era of personalized oncology therapy and has the ability to detect mutations in ERBB receptors. Case presentation We present a patient with metastatic cutaneous squamous cell carcinoma who failed surgery, radiation, and anti-PD1 therapy, but showed clinical response to a drug targeting an ERBB3 mutation identified with NGS. Following initiation of the drug lapatinib, this patient exhibited dramatic tumor regression in the skin, soft tissue, bone and nerves. Conclusions Cutaneous squamous cell carcinoma is the 2nd most common skin cancer in humans and future investigation of ERBB2 targeted therapies may provide an effective treatment strategy for patients with mutations in the ERBB2/3 pathway.